Photobiomodulation and physical exercise on strength, balance and functionality of elderly women - Patricia Gabrielli Vassão; Renata Luri Toma; Hanna Karen Moreira Antunes; Ana Claudia Muniz Renno (Editora Champagnat, 2018)
Abstract Introduction: Aging is associated with structural changes in muscle tissue, which leads to the loss of functional independence. The preservation of the muscle strength through strength training, and recently, low-level laser therapy (LLLT), has high clinical significance. Objective: to investigate the effects of photobiomodulation (PBM - 808 nm, 100 mW, 35.7 W/cm2 and 7 J) associated with a strength training program on quadriceps muscle strength, balance and functional capacity in elderly women. Methods: Thirty-five healthy women between 60 to 70 years old were divided into two groups: Placebo Group (n = 13) and Active Group (n = 14). The exercise protocol consisted of knee flexion-extension exercise followed by application of PBM placebo or active, twice a week for 8 consecutive weeks. Results: showed a significant increase in 6MWT (p = 0.001), SPPB (p = 0.006) and 1-MR (p = 0.001) in both groups. The strength training program associated with PBM active improved a significant increase, relative to baseline, to the right medial/lateral stability index (p = 0.007) and decrease in the Fall Risk Test (p = 0.005). Conclusion: the strength training produced a significant increase of muscle strength and functionality and when combined with the PMB it was significant in the improvement of postural stability and decrease of fall risk.